2021
DOI: 10.3390/diagnostics11050796
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia in Stroke Patients, Multiple Sclerosis and Parkinson’s Disesase

Abstract: Background: Stroke (S), multiple sclerosis (MS), Parkinson’s disease (PD) are chronic neurological diseases that are a challange for public health and represent a real social problem. Physical activity (PA) improves functional performance, reduces various symptoms in PD and MS, in stroke- reduced neurological impairment of patients and provides a chance for independence. One of the main obstacles in successful rehabilitation is patients’ movement passivity. The reason might be the psychological aspects, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…This area of disease has so far been poorly researched, and reports are scarce. The presented results, as well as previous studies, indicate that the scale of this problem is large [ 22 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This area of disease has so far been poorly researched, and reports are scarce. The presented results, as well as previous studies, indicate that the scale of this problem is large [ 22 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 82%
“…Kinesiophobia in people suffering from neurological diseases is still relatively poorly understood [ 22 ]. Few publications on the problem of kinesiophobia in MS patients indicate its association with pain and fatigue and, consequently, its impact on quality of life [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…As in our study, other authors have also shown a high prevalence of kinesiophobia in elderly stroke patients. 11 , 12 According to Wasiuk-Zawada et al, the incidence of kinesiophobia varied depending on the degree of motor disability according to Rankin, including 83.3% of patients with mild disabilities and 73.1% of patients with moderate disabilities. 12 In the above studies 11 , 12 and in our study, kinesiophobia was defined on the basis of the TSK criterion, which allowed for a comparative analysis of the frequency of this phenomenon, which turned out to be high in the majority of stroke patients in studies from various centers.…”
Section: Discussionmentioning
confidence: 99%
“… 11 It was shown that the occurrence of kinesiophobia in stroke patients was quite common and it concerned even more than 80% of patients. 12 In another study it was observed that patients with stroke had mild kinesiophobia, which was related to a fear of falling. 13 The above-cited publications, the only ones in the available literature, show that the problem of the occurrence of kinesiophobia in patients after stroke has not been well recognized so far, and it must be admitted that learning about this phenomenon would facilitate planning the methods of effective post-stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 98%
“…The wide range of symptoms that can occur in MS patients are showcased through two manuscripts by outlining the rate of kinesiophobia and neurogenic lower urinary tract dysfunction. Wasiuk-Zowada et al administered the Tampa scale of kinesiophobia questionnaire (quantifying the fear of movement) to 81 MS patients, and the kinesiophobia diagnosis (>37 points on the questionnaire) was present in 18.5% of patients in the low-disability category to 74.2% and 65.2% in the more-disabled patients [ 9 ]. Based on these findings, MS rehabilitation studies should account for the high kinesiophobia rate in more-disabled MS patients, which could significantly influence the recruitment rate and persistence in the program.…”
mentioning
confidence: 99%